Wizerunek młodych Rosjan i Polaków w prozie przedstawicielek młodego pokolenia – Iriny Dienieżkiny i Doroty Masłowskiej (Дай мне!, Song for lovers, Wojna polsko-ruska pod flagą biało-czerwoną) - Polak, Andrzej (Acta Polono-Ruthenica, 2011)
The article contains a comparison of the works by the representatives of the youngest genera- tion of writers: Dorota Masłowska and Irina Dienieżkina. The author makes a short review of the opinions on the characteristics and attitudes regarded widely as stereotypical and then tries to determine to what extent, and if at all, they are translated into the behaviour and views of Masłowskas and Dienieżkinas characters? What brings closer, and what makes these two youth subcultures different? Seeking answers to such a question, the author reflects three areas of human activity: love, male-female relationships and a language (the youth culture slang). The analysis determines the assimilation of these two youth communities, first of all due to the common fascination with mass culture, pop culture. The said assimilation is accompanied by the simultane- ous disappearance of the characteristics widely recognised as stereotypical.